2016
DOI: 10.1016/j.ijbiomac.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Thermostabilization of Bacillus subtilis GH11 xylanase by surface charge engineering

Abstract: Aiming to improve thermostability of the mesophilic xylanase A from Bacillus subtilis (XynA), five single mutants (S22E, S27E, N32D, N54E and N181R) were used to construct a random combinatorial library, and screening of this library for thermostable XynA variants identified a double mutant (S22E/N32D). All 6 mutants were expressed in Escherichia coli (BL21) and purified. Xylanase activity showed all mutants have an optimum catalytic temperature (Topt) of 55°C, and with the exception of the S27E mutant, a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…Sanchez-Alponti et al created and characterized single mutants individually replacing five residues in the mesophilic xylanase of B. subtilis with homologous residues from thermophilic enzymes. When the five mutants were combined in a random combinatorial library, a double mutant with improved specific activity and thermal stability was obtained [ 77 ]. Yardimci and Cekmecelioglu used Box–Behnken response surface methodology to optimize xylanase production in a co-culture of B. subtilis and Kluyveromyces marxianus , which improved the xylanase yield 4.4-fold (reached 49.5 IU/mL) compared to the initial un-optimized single culture [ 76 ].…”
Section: Xylanasesmentioning
confidence: 99%
“…Sanchez-Alponti et al created and characterized single mutants individually replacing five residues in the mesophilic xylanase of B. subtilis with homologous residues from thermophilic enzymes. When the five mutants were combined in a random combinatorial library, a double mutant with improved specific activity and thermal stability was obtained [ 77 ]. Yardimci and Cekmecelioglu used Box–Behnken response surface methodology to optimize xylanase production in a co-culture of B. subtilis and Kluyveromyces marxianus , which improved the xylanase yield 4.4-fold (reached 49.5 IU/mL) compared to the initial un-optimized single culture [ 76 ].…”
Section: Xylanasesmentioning
confidence: 99%
“…After two rounds of site-saturated mutagenesis, double mutation S3F/D35I contributed to the enhanced ∆ T m value of 7.8 °C and improved the thermostability of Tl Xyn11B at 50–70 °C. The T m value of the surface charge engineered XynA 17 was improved from 330.4 K to 332.4 K, which was significantly lower than the improvement of Tl Xyn11B (333.0 to 340.8 K); on the other hand, the Tl Xyn11B activity (8,300 U/mg) was much higher than the mutated XynA activity (47 U/mg). Another intriguing finding is that the improved thermostability has no impairment on the enzyme activity (Table 2 ).…”
Section: Discussionmentioning
confidence: 73%
“…It is found that the N-terminal sequence plays a key role in the stability of GH11 xylanases. By replacing the N-terminus with thermostable ones 13 , 14 , introducing a disulfide bond to the N-terminus 15 , substituting the N-terminal residues 16 , and optimizing the surface charge interactions 17 , the thermostability of GH11 xylanases have been successfully improved. The underlying mechanism has been ascribed to the more amino acid interactions and decreased unfolding entropy 13 .…”
Section: Introductionmentioning
confidence: 99%
“…They used MD simulations to compare residue flexibility and salt bridge occupancy between TLX and BCX at temperatures between 25° and 70° C. TLX has a larger number of intramolecular interactions among residues in the ‘fingers’ domain as well as more favorable interactions between side chains and solvent. Building off of the results from Vieira et al 90,91 , Alponti et al grafted charges from a thermophilic GH11 xylanase into a mesophilic scaffold 92 (Figure 3C). In total, five mutations were made in the ‘fingers’ domain: S22E, S27E, N32D, N54E, N181R.…”
Section: Modulating Protein Stabilitymentioning
confidence: 97%